Lifecycle risk assessment on the sustainable development of upgrading energy projects using abandoned mines: An ISM-BWM method. (December 2022) - He, Jiaming; Wu, Yunna; Yong, Xingkai; Ke, Yiming; Tan, Qinliang; Liu, Fangtong
Highlights: This paper examines the risk of the abandoned mine upgrading energy projects. A linguistic evaluation procedure under Pythagorean fuzzy environment is proposed. Combination of best worst method and interpretive structure model is introduced. The lifecycle risk distribution for five means of technologies is concluded. Risk response of each upgrading alternative and policy implications are suggested. Abstract: Mining industries have left countless opencast and underground mines in Northwest China without careful disposal for the past decades. The authorities encourage rehabilitation of abandoned mines under the green development strategy, while the path for relevant enterprises remains unclear so far. This paper thus studies the risk distribution of energy alternatives for abandoned mine upgrading. 5 types of upgrading alternatives are studied, including both generation and storage ones. A lifecycle risk system for the alternatives is established for the first time. 12 risk factors extracted through literature and expert involvement are classified as decision-making, implementation, and operation stages. Then, subjective judgements are converted into hesitant fuzzy linguistic term sets under Pythagorean fuzzy environment. And the best worst method combined with the interpretive structure model is firstly introduced to calculate relative importance based on mutual influence. Results indicate that photovoltaic and heat storage stations are generally the safest alternatives, with the lowest risk level ranging from 0.7166 to 0.8073 and hesitant degree from 0.3473 to 0.4248. Moreover, risk response measures for each alternative and policy implications for local governments are first raised to put forward AMUEP development. The analytical framework could also be applied elsewhere for smooth rehabilitation of abandoned mines.